DESIGN OF MODEL-BASED GEOGRAPHY LEARNING ENVIRONMENT TO CREATE SCHOOL FUN - singgih prihadi (GeoEco, 2018)
The research was distributed by the demands of professional teachers in carrying out the mandate to develop and implement creative and productive learning involving learners as well as their role actively. The learning process that facilitates the needs of learners and of innovative designed will be able to create an atmosphere of learning fun and meaningful for learners. Especially for geography teachers who want to create a geography learning with fun and meaningful then must master the application of model-based learning environment. This initial research is the study of the introduction in the form of needs analysis in the development of a prototype model of learning geography-based environment for creating school fun. Needs analysis is done to strengthen basic product development model so that the expected results have great benefits for teachers. In the needs analysis will be known the level of understanding of the geography teacher in Surakarta City against the application of the model of learning geography-based environment. This learning model of product development done because of early observations of known low learning motivation of the learners follow learning geography in school.The research method used was Research and Development version of the Borg and Gall. Phases of this research is the first step of the model of Research and Development. At this stage of the preliminary study it, researchers attempted to dig in depth about the perception, skill, and the suitability of the curriculum learning focussed experiences related to the geography-based environment for creating school fun. Engineering data collection done by interview and Focus Group Discussion (FGD) and geography teachers in the city of Surakarta.From research conducted, produced conclusions that: 1) the perception of teachers in understanding the concept of geography-based learning model development environment is already good enough. Teachers describe teaching experience by leveraging the model-based learning environment. 2) teacher skills in teaching using model-based geography learning environment is already quite good, though there is still that have not been put into practice appropriate procedures systematically. This has an impact on the learning process becomes not interesting for learners. 3) Utilizing the geography learning resource in the form of an environment capable of answering the demands of the scientific approach to skills achievement Curriculum on 2013.